Investigation of Trace Element Levels and Toxic Metals in Obese Children: A Single-Center Experience - Sultan Kaba; Sinan Kılıç (AVES Yayincilik, 2024)
Objective: The complete role of factors contributing to the pathogenesis of childhood obesity remains to be fully elucidated. Limited research has addressed trace elements in the context of child obesity. Our objective was to assess trace element and lead (Pb), copper (Cu) (are toxic metal) levels in both healthy and obese children, and to investigate the potential correlations between these elements and obesity-related anthropometric measurements, lipid profiles, as well as insulin and glucose levels. Materials and Methods: Furnace atomic absorption spectrophotometry was employed to measure the concentrations of trace elements in the serum. Additionally, fasting glucose, insulin, and lipid levels were determined in obese children (body mass index ≥ 95th percentile for age and sex), along with 50 healthy children. Only the obesity group underwent an oral glucose tolerance test (OGTT). Results: Significantly reduced levels of Fe, Mg, Zn, and Co were observed in obese children, whereas Cu, Pb, and Mn levels were elevated (P < .001, P <.001, P = .002, P = .008, P <.001, P = .001, P = .007, respectively). Significant positive correlations were found between the 2-hour glucose level in OGTT and Mn (P = .013), as well as between peak insulin and insulin levels at the 30th and 60th minutes, and Fe (P = .001, P = .025, P = .001). Conclusion: This study indicates that an imbalance in trace element levels and the accumulation of Pb may be associated with obesity, while levels of Mn and Fe may be linked to glucose intolerance.